VERBA SERIAL DALAM BAHASA INDONESIA - Dita Oktaviana; Mukhlish Mukhlish (CARAKA, 2015)
The purposes of this reseach is (1) describing the characteristics of serial verbs in Indonesian language; (2) describing the serial verb formingn patterns in Indonesian language; (3) describing the relation of serial verbs in serial verbs Indonesian language. This research is qualitative research. Data collection methods in this study is distribution method with vanished technique, insertion technique, turning technique, and expand technique. The results as follows. (1) The characteristic of serial verbs in Indonesian language consists of (a) serial verbs formed by two verbs; (b) serial verb predicate as lying side by side; (c) serial verbs form a double clauses; and (d) serial verbs have the same aspect and negation. (2) The serial verb forming pattern of Indonesian language is (a) V1 transitive+V2 transitive, (b) V1 transitive+V2 nontransitive, (c) V1 nontransitive+V2 transitive, and (d) V1 nontransitive+V2 nontransitive. (3) The relation of serial verbs in serial verbs Indonesian language is (a) the relation which explain the purpose, (b) the relation which explain cause effect and effect cause, (c) the relation which explain time similarity, (d) the relation which explain time sequence, and (e)Â  the relation which explain the complement.